Azote asymétrique: racémisation et échange de deutérium dans des complexes macrocycliques - E. Sledziewska; L. Plachta; D. VonderSchmitt; K. Bernauer (CHIMIA)
Racemization kinetics of the Ni2+- and Cu2+-complexes of three macrocyclic ligands with coordinated nitrogen as asymmetric centers have been measured. Reaction rates of all the complexes are first order in complex concentration and in hydroxide ion concentration. Arrhenius activation energies are in general smaller for the copper compounds. Deuteration rates were measured for the Ni2+-complexe–[Ni(CH3)6-1,7-CT](NCS)2 (structure I) in a mixture of D2O and d6-dimethyl-sulfoxide at low pD-values. These rates are found to be higher by a factor of 400 than racemization rates under the same conditions, indicating mainly retention of configuration about the nitrogen center, as is found for inert N-asymmetric CoIII- and PtII-complexes.